Mediating Effect of Loneliness on the Relationship between Self‑esteem and Cyberbullying among University Students: Gender Difference as a Moderator - Prashanth, Talwar Yadar; Mohamed Sharif, Mustaffa; Mohd Fadzil, Abdul Rahman; Gaddafi, Ismaili (Wolters Kluwer - Medknow, 2024)
Objective: Digital media in education is important to students’ success. However, the double-edged nature of digital media poses a potential risk of cyberbullying (CYB). Feelings of loneliness (LON) and perceptions of being rejected by peer group have often been associated with CYB. The present study explores the mediating effect of LON on the relationship between self‑esteem (SE) and CYB behavior, especially among university students. In addition, the moderator effect of gender on SE and CYB behavior was also investigated. Materials and Methods: A convenience sampling technique was employed in this cross‑sectional study, participated by 231 university students. The participants completed a self‑report inventory consisting of Cyber Victim and Bullying Scale, UCLA LON Scale Version 3 Rosenberg’s Self Esteem Scale‑10, and Socio demographic profile questionnaire. Data were analyzed using Structured Equation Modelling and Hierarchical regression. Results: Simple mediation analysis depicted that the association between SE and CYB was significantly reduced, in the presence of LON as the mediator (c’; = −0.27, P = 0.000), indicating a partial mediation. In other words, LON partially mediated the effect of low SE on CYB. Hierarchical regression analysis revealed a potentially significant moderation between gender, SE, and CYB behavior (R2 change = 0.028, P = 0.001). Conclusion: The present study illustrated that LON had a mediating effect on the relationship between SE and CYB behavior. Besides this, gender difference was found to be a noticeable cause in the perpetration of CYB behavior. These findings indicate that SE and LON‑oriented interventions may successfully address CYB behavior.